2020
DOI: 10.1001/jamanetworkopen.2020.5252
|View full text |Cite
|
Sign up to set email alerts
|

Association of Pharmacist Prescription With Dispensed Duration of Hormonal Contraception

Abstract: IMPORTANCE Since 2016, 11 states have expanded the scope of pharmacists to include direct prescription of hormonal contraception. Dispensing greater than 1 month's supply is associated with improved contraceptive continuation rates and fewer breaks in coverage. Scant data exist on the practice of pharmacist prescription of contraception and its outcomes compared with traditional, clinic-based prescriptions. OBJECTIVETo compare the amount of hormonal contraceptive supply dispensed between pharmacists and clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 37 publications
0
39
0
Order By: Relevance
“…A study conducted in 2019 reported that pharmacists are more likely to prescribe 6 months or more of contraceptives supply at a time. 39 This practice is supported by the protocol on contraceptive prescribing used in Minnesota, which does not indicate limitations on the number of refills that pharmacists can prescribe. As indicated in the protocol, pharmacists in Minnesota are required to provide the patient with a written record that includes the number of refills approved.…”
Section: Limitations Of the Policymentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted in 2019 reported that pharmacists are more likely to prescribe 6 months or more of contraceptives supply at a time. 39 This practice is supported by the protocol on contraceptive prescribing used in Minnesota, which does not indicate limitations on the number of refills that pharmacists can prescribe. As indicated in the protocol, pharmacists in Minnesota are required to provide the patient with a written record that includes the number of refills approved.…”
Section: Limitations Of the Policymentioning
confidence: 99%
“…11 Allowing pharmacists to prescribe 6 months or more of contraceptive supply has the potential to improve contraceptive adherence and decrease unintended pregnancies and should be supported across states' policies. 39 Expanding access through pharmacist-prescribing places Minnesota pharmacists in a position to ensure safety in the prescribing and use of contraceptives. Patients questioned the safety of contraceptives and reported concerns about their adverse events.…”
Section: Limitations Of the Policymentioning
confidence: 99%
“…Patients who are able to receive the entire year of contraception in one fill are more likely to continue their method [ 56 ]. Pharmacists more frequently prescribed a 6-month or more supply of contraception at one time compared to other providers in one study [ 57 ]. Pharmacist-prescribed contraception does significantly positively impact access to contraception care.…”
Section: Evidence Against Opposition To Pharmacist Contraception Smentioning
confidence: 99%
“…Receiving healthcare directly from a pharmacist does not require an appointment, and many pharmacies have hours that are expanded from typical medical clinic hours, allowing patients to seek services at times that are convenient for them. Additionally, findings from a recent study show that women receiving contraception from pharmacists were younger, had less education, and were more likely to be uninsured than women seeing traditional healthcare providers [10]. It has also been found that patients who receive a 6 month or greater supply of contraception have higher rates of contraceptive continuation and adherence [6,10].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, findings from a recent study show that women receiving contraception from pharmacists were younger, had less education, and were more likely to be uninsured than women seeing traditional healthcare providers [10]. It has also been found that patients who receive a 6 month or greater supply of contraception have higher rates of contraceptive continuation and adherence [6,10]. These findings suggest that the pharmacist prescribing of contraception allows for an improved access to birth control methods, especially in underserved populations, and provides a promising strategy to promote consistent use of contraception [11].…”
Section: Introductionmentioning
confidence: 99%